(untitled) (JISTECH: Journal of Information Science and Technology, 2023)
The recent development is indirectly resulting in an increase of the need of gravel materials. Thus, management efforts should be importantly implemented in mine operations. To run a new mine operation, an analysis regarding finance planning would be needed in order to determine the amount of cost spent in the whole activities of mine operation. One critical point of the financial analysis is the breakeven point method. This method is utilized to estimate the minimum quantity of production based on the operational costs spent. Breakeven point method would also show the correlation patterns between sale volumes, production costs, and return levels in each level of sales. In addition, several alternatives in terms of production and cost efficiency can be derived by implementing this approach. The results showed that the breakeven point of mine activities operated by Pulau Lemon company was Rp. 2,376,444 per hour, while the minimum quantity of production was 8.06 tonnes per hour. The implication of the results was that the company should operate above the breakeven point to ignore such financial loses.